The Effect of Liquidity, Profitability, Solvency, Activity, and Capital Structure on Company Value with Dividend Policy as an Intervening Variable in Healthcare Subsector Companies Listed on the Indonesia Stock Exchange in 2019 - 2023 - Sugianto, Arif; Sukoco, Agus (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This research aims to find out the impact of the financial ratio of liquidity, profitability, solvency and capital structure on the value of the company with the policy of dividend as an intervening variable on the healthcare subsector companies listed on the Indonesian stock exchange period 2017-2019. This is a causality study that seeks cause-effect relationships between three variables: an exogenous (free or independent) variable that affects, an endogenic variable (binding or dependent) that is affected, and an intervening variable which affects the relationship between the two indirectly and not directly observable. Design/methodology/approach: This researcher uses inferential quantitative methods. The research used financial reports on healthcare subsector companies listed on the Indonesian Stock Exchange in 2019, 2020, 2021, 2022 and 2023 by accessing the website www.idx.co.id, the corporate site on the research object, and sites that support the enrichment of research material. Sampling techniques used purposive sampling and produced a sample of 36 healthcare subsector companies. The source of data used in this study is annual secondary data. Data analysis using SmartPLS 3.2.9. Finding: The results of the analysis showed that liquidity had a positive and significant influence on the value of the company. Results of analysis indicated that profitability had a negative and no significant impact on the company's value. The result of analysis revealed that the profitability has a negative influence and did not have a significant effect on the corporate value. There is no direct and nonsignificant influence between profitability on the company's value and the policy of dividends as the intervening variable is not proved to be mediated. The analysis results there is a positive and significant direct influence on the value of the company with the dividend policy as the intervenient variable was proven to be Mediated. There is a direct and significant positive influence among the capital structure on the corporate value with the dividend policy of the intervened variable as the mediated variable. Paper type: Research paper